Age, weight and decompression sickness in rats - Buzzacott, Peter; Theron, M.; Mazur, A.; Wang, Q.; Lambrechts, K.; Eftedal, I.; Ardestani, S.; Guerrero, F. (2016)
© 2015 Taylor and Francis. Objective: The aim of this study was to determine if, after controlling for weight, age is associated with decompression sickness (DCS) in rats. Methods: Following compression-decompression, male rats aged 11 weeks were observed for DCS. After two weeks recovery, surviving rats were re-dived using the same compression-decompression profile. Results: In this experiment, there was a clear difference between DCS outcome at ages 11 or 13 weeks in matched rats (p = 0.002). Discussion: Even with weight included in the model, age was significantly associated with DCS (p = 0.01), yet after removal of weight the association was much stronger (p = 0.002). Conclusion: We believe that age is likely to be found associated with the probability of DCS in a larger dataset with a wider range of parameters, after accounting for the effect of weight.